2019
DOI: 10.1096/fj.201901231r
|View full text |Cite
|
Sign up to set email alerts
|

The olfactomedin‐4 positive neutrophil has a role in murine intestinal ischemia/reperfusion injury

Abstract: Olfactomedin-4 (OLFM4) identifies a subset of neutrophils conserved in both mouse and man, associated with worse outcomes in several inflammatory conditions. We investigated the role of OLFM4-positive neutrophils in murine intestinal ischemia/reperfusion (IR) injury. Wild-type (WT) C57Bl/6 and OLFM4 null mice were subjected to intestinal IR injury and then monitored for survival or tissues harvested for further analyses. In vivo intestinal barrier function was determined via functional assay of permeability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The authors hypothesized a potential mechanism for this observation, in which activated neutrophils next to the injury secrete OLFM4 into the environment leading to enhanced iNOS production by macrophages and injured tissue. This leads to an impaired intestinal barrier [21]. We observed a moderate/high expression of OLFM4 in affected intestinal tissue and in immune cells of in ammatory intestinal regions in cases of NEC and volvulus and are therefore able to support these observations.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The authors hypothesized a potential mechanism for this observation, in which activated neutrophils next to the injury secrete OLFM4 into the environment leading to enhanced iNOS production by macrophages and injured tissue. This leads to an impaired intestinal barrier [21]. We observed a moderate/high expression of OLFM4 in affected intestinal tissue and in immune cells of in ammatory intestinal regions in cases of NEC and volvulus and are therefore able to support these observations.…”
Section: Discussionsupporting
confidence: 74%
“…Alder et al con rmed an association of these OLFM4 neutrophils with a worse outcome during sepsis [14]. Moreover, Levinsky et al observed that OLFM4 null mice are protected from death during sepsis and showed less intestinal barrier dysfunction, implicating that OLFM4 might contribute essential pathogenic aspects to the in ammatory process [21]. Furthermore, they described the central involvement of OLFM4-positive neutrophils in the pathologic process leading to intestinal damage and mortality after intestinal ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018 it was discovered that mouse neutrophils also display a bimodal distribution of Olfm4 [5]. Olfm4-expressing mice displayed more severe mucosal damage than Olfm4-deficient mice in a model of intestinal ischemia-reperfusion injury, with increased nuclear factor-kappaB and inducible nitric oxygen synthase activation, in a neutrophil-mediated manner [38]. Recently, it was shown that juvenile Olfm4-decifient mice are protected from sepsis, and display lower levels of acute kidney injury than in wild-type mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that neutrophils secret OLFM4 into the environment and stimulated a downstream inflammatory response by inducing macrophages to produce inducible nitric oxide synthase (iNOS). 28 Moreover, different origins of OLFM4 (eg, epithelium, neutrophils, stem cells) might exert different effects during inflammation. Kuno et al showed that OLFM4 secretion led to antimicrobial activity, while cytoplasmic OLFM4 played an anti-apoptotic role in human intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%